Свойства и области применения металлизированных тонкодисперсных алмазных и кубонитовых порошков - Дуда, Т.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The effect of the metallization of finely dispersed synthetic diamond and cBN powders with
nickel on their physical and operation properties and grain composition has been studied. It has been shown that finely dispersed metallized powders of superhard materials can be successfully used in production of tools for machining natural diamonds, hard alloys, and stones.